Substructure works for single storey housing project (Case study: Installation of foundation and ground beam) / Muhammad Hazman Hashim - Hashim, Muhammad Hazman (2016)
HMJ ELITE TRADE was established in 2010 in Kota Bharu, Kelantan ideas from Mr. Hashim bin Haji Mat Jali family. This company was registered under the name of Mr. Mohamad Hakikie bin Hashim and Mrs. Salwati daughter Yussuf and it was established to engage actively in the wholesale / retail and also general contractors and street.The manager of this company, Mr. Hashim bin Haji Mat Jali, who is also a graduated student from University Sumatra Utara(1976) hiring worker which is only graduated in course that related to business.For example, all shareholders are composed of 5 members have a degree in business. HMJ ELITE TRADE office which is also located at the house of Mr. Hashim bin Haji Mat Jali, has been running for 5 years in business project.The purpose of moving the office from Kota Bharu to his own house is that all construction work as well as retail can run smoothly with their own family members help him.Beside that, it also makes it easier for clients to meet with management to discuss business matters.